Mallorca, Menorca & Ibiza - Micula, Grzegorz; Sobieraj,Katarzyna; Pasieczny, Robert G.; Nowakowski, Eligiusz; Pasieczny, Robert G.; Demko, Anna Moczar (Eyewitness travel guides., 2014)
A travel guide to Mallorca, Menorca and Ibiza that leads you to the best attractions of the Balearic islands. Featuring photographs, illustrations and maps, it explores the culture, history, architecture and art of these islands and reveals the best in entertainment, outdoor activities, wildlife and Spanish fiestas.